Registration of BTx623ms8, a New and Easily Identifiable Nuclear Male Sterile Mutant in Sorghum. Issue 2 (11th January 2018) - Xin, Zhanguo; Chen, Junping; Jiao, Yinping; Gladman, Nicholas; Hayes, Chad; Burow, Gloria; Emendack, Yves; Burke, J. J.
Abstract : The USDA–ARS has released a new nuclear male sterile sorghum [ Sorghum bicolor (L.) Moench] mutant BTx623ms8 (Reg. No. GS‐786, PI 682727). Previously, seven sorghum nuclear male sterile mutants have been reported, but three are no longer available. Here we register a new nuclear male sterile mutant isolated from a mutagenized BTx623 mutant library that is genetically different from any of the four male sterile mutants currently available. The ms8 mutant had microscopic transparent anthers that abort early during microsporogenesis. It can be easily identified at early stages of anthesis by the appearance of prominent white, hairy stigma, rather than yellow anthers as seen in BTx623 and all other fertile sorghum accessions. We have developed BC6 F2 seeds that produce approximately 50% male sterile plants by pollinating the homozygous ms8 mutants with the heterozygous fertile plants. The ms8 is a single recessive nuclear gene mutation and can be easily bred into other sorghum lines through recurrent backcrossing, broadening the utility of this easily recognizable nuclear male sterility.